Is There A Link Between Finance, Investment and Growth?: Experiences of Developing Countries - Losina Purnastuti (Universitas Negeri Yogyakarta, 2005)
Artikel ini mencoba mencari bukti-bukti empiris di berbagai negara mengenai pernyataan Bank Dunia –